NIGROMANCIA, PRESTIDIGITACION E HIPNOTISMO EN LA CIUDAD DE MEXICO (1864-1910) - Urbina Gaitán, Chester (Universidad de Costa Rica, 2014)
The shows necromantic, prestidigitation and hypnotism made in Mexico city, by foreignartists between 1864 and 1910, were of exclusive access from the bourgeoisie capital,because they were presented in the main theaters and centers of socialization of thissocioeconomic group. On the submission of such acts must differentiate fraudulent showsand who had scientific explanations about their experiments, contributing to the Mexicanhad contact with new theories and scientific currents.